Attraction and Ease of Access as Determinants of Interest in Visiting Camping Grounds in Sentul - Margareth Laretta Arifin (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The tourism sector is experiencing significant growth in the post-pandemic era, with nature-based tourism — such as camping grounds — gaining popularity as people seek to break away from routine and find safe, open-air recreational spaces. This research aims to analyse the effect of attractiveness and accessibility on tourists' intention to visit nature-based camping ground tourism destinations in the post-pandemic era. A quantitative research approach was employed using a survey method. Data were collected through structured questionnaires distributed to respondents who had previously visited, or expressed a strong intention to visit, a camping ground. Purposive sampling was applied, yielding a total of 136 respondents, which exceeds the minimum required sample size of 60 respondents. The study utilised primary data, which were analysed using the Partial Least Squares (PLS) method. The results reveal that attractiveness has a positive effect on tourists' intention to visit camping ground destinations. Accessibility likewise shows a positive influence on visiting intention. These findings indicate that tourists are more likely to visit camping grounds that offer appealing natural attractions, unique experiences, and adequate supporting facilities, as well as convenient and accessible routes. Tourism managers are therefore encouraged to enhance attractiveness and improve accessibility in order to increase tourists' visiting intention, particularly in support of the recovery and development of nature-based tourism in the post-pandemic era.